On the oscillatory solutions of nonlinear hyperbolic differential equations by the decomposition method - Asil, V; Bulut, H; Evans, DJ (Taylor & Francis Ltd, 2004)
In this study, the decomposition method for the approximate solutions of the linear and nonlinear deterministic or stochastic differential equations, is given by the decomposition (Adomian) and has been investigated in general. In applying the method to the nonlinear deterministic hyperbolic equations, the concept of the Adomian polynomials has been explained and one application of the method given for the general state is obtained.
Keywords: nonlinear hyperbolic equation; the decomposition method